A comparative study of the preference for fiction between young adults and adults in the Greater Manila Area - Judalena, Sheila Kristeen N.; Sison, Josephine C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
Studies have been made on the reading preferences of children, young adults, and adults all over the world. Few, if any on record, deal solely with comparing the extent of interest for fiction between young adults and adults in a given community. This study shows that young Filipino adults read more fiction books than Filipino adults. It also shows which frequency of reading fiction and which type of fiction (e.g. romance, science, adventure, suspense, comic, etc.) is preferred among classes subdivided according to the following criteria: age group (young adult and adult); low, middle, and high-income families.
The study was limited to the reading activities of 200 library users in the Greater Manila Area, particularly, the Quezon City Public Library and Makati City Public Library. The participants were chosen by means of stratified random sampling where there are 100 participants per library, and out of each 100, there are 25 female young adults, 25 male young adults, 25 female adults, and 25 male adults. Thus, for the two libraries, there were 100 male and female young adults, and 100 male and female adults. Examples of such participants are businesspersons, employees, professionals, and students.
A comprehensive investigation was made on the preference or non-preference for fiction of young adults and adults, the income-brackets that the participants belonged to, the frequency of reading fiction, and the type of fiction that is most preferred by the age groups. Family income and age were taken as factors affecting the reading activities of the participants.
The primary tool used in gathering the data for this investigation was a two-part questionnaire. The first part dealt with personal data such as age, gender, working status, and gross family income of the respondent. The second part dealt with the reading activities of the respondents where reading preference and frequency were concerned. For special cases where the respondent preferred to be interviewed, the same questionnaire was used as the basis for the interview. Since the libraries participating in this investigation represent the types found in the Greater Manila Area, any conclusions made apply only to the library users of this particular area.
Findings show that most of the respondents come from middle-income families. There are very few coming from high-income families. The ages of the respondents range from 13 years to 62 years old. Out of 100 young adults, 99 go to school. Out of 100 adults, 95 are employed, professionals, or in business, while 5 are pursuing a higher degree in school. For the low and middle-income groups, the inverse proportion of the preference or non-preference for fiction is significantly high between age groups. Most young adults read fiction thrice a week whereas most adults read fiction twice a year. The fiction sub-genre preferred by most young adults is the historical novel, followed by short stories, and detective fiction. As for adults, short stories are most preferred, followed by the historical novel and romance. This study is significant in determining which type of fiction books can help attract clientele, in order to market the library and its services further.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Adulthood -- Books and reading -- Philippines -- Manila Metropolitan Area; Fiction -- Stories, plots, etc; Reading interests -- Philippines -- Manila Metropolitan Area; Young adults -- Books and reading -- Philippines -- Manila Metropolitan Area